Effect of high planting density and foliar fungicide application on the grain maize and silage and methane yield - Testa, Giulio; Reyneri, Amedeo; Blandino, Massimo (Italian Journal of Agronomy, 2018)
The research investigated ways to enhance maize yield in intensive maize cropping system by evaluating the effect of high planting densities combined with foliar fungicide treatments. The considered assessments were fungal leaf disease, biomass and grain yield and methane production through anaerobic fermentation. The experiment was conducted in the years 2012 and 2013. The treatments compared at each location were factorial combinations of two plant densities and three fungicide applications. A standard planting density (StD, 7.5 plants m–2 on a 0.75 m interrow spacing) was compared with the high density (HiD, 10 plants m–2 on narrow 0.5 m inter-row spacing). Two fungicides, pyraclostrobin at 0.2 kg AI ha–1 and a mixture of pyraclostrobin and epoxiconazole at 0.2 and 0.075 kg AI ha–1 respectively, were applied at the tassel emergence stage and compared with an untreated treatment. The HiD system positively increased the silage maize yield (+16%), grain (+17%) and methane yield per hectare (+19%) in comparison to the StD. The fungicide application significantly restrained foliar disease symptoms only in 2012. Fungicide did not affect plant silage composition (protein, starch or fibre content) and methane yield, conversely it significantly increased grain yield for both planting density systems (+5%). The overall boost in yield obtained by combining both strategies in an intensive system, HiD combined with the fungicide, was +24% for methane and +21% for grain yield compared to StD without fungicide application. This work proved that an intensive high planting system with up to 10 plants m–2, supported by leaf fungicide treatments, can lead to a real yield enhancement of both maize grain and silage.